PENGARUH PENERAPAN SUSTAINABILITY REPORTING, EFEKTIVITAS PENGENDALIAN INTERNAL, DAN ETIKA AKUNTANSI TERHADAP TRANSPARANSI LAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022–2024 - Silvi Oktaviani; Taufiq Andre Setiyono (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study aims to examine the effect of sustainability reporting, internal control effectiveness, and accounting ethics on financial statement transparency in companies listed on the Indonesia Stock Exchange (IDX). Financial statement transparency is an important aspect of enhancing corporate accountability and increasing stakeholders' trust in the information disclosed by companies. This study employed a quantitative approach using secondary data obtained from annual reports, financial statements, and sustainability reports for the 2022–2024 period. The sample was selected using a purposive sampling technique, resulting in 48 companies with a tota of 144 observations. Data were analyzed using multiple linear regression with the assistance of SPSS software.